Myoelectrically Controlled FES to Enhance Tenodesis Grip in People With Cervical Spinal Cord Lesion: A Usability Study - Thorsen, Rune; Dalla Costa, Davide; Beghi, Ettore; Ferrarin, Maurizio (Frontiers in Neuroscience, 2020)
People with tetraplegia are often lacking grip strength, causing impairment in activities of daily living. For them, improving hand function is a priority because it is important for autonomy and participation in daily life. A tendon transfer surgery may be an option to improve the tenodesis grip, but it is an invasive procedure. Alternatively a similar effect can be produced, using a non-invasive method. We have previously described how myoelectrically controlled functional electrical stimulation (MeCFES) can be efficient for enhancing grip strength, using a one channel research prototype with wired connections to surface electrodes. In this paper we focus on the usability for activities of daily living and how it can fulfill an actual need. We recruited 27 participants with a cervical spinal cord lesion (C5-C7) for this trial. They tested the device in 12 sessions of 2 h each, in which the participants performed self selected activities involving the tenodesis grip. User centered outcomes were validated questionnaires: the Individually Prioritized Problem Assessment (IPPA) and the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST). Furthermore, they were asked if they found the device useful for continued use in daily life. The device facilitated prioritized activities for all participants. The IPPA change score was 4.6 on average (STD:3.5, effect size:1.3), meaning that the system greatly facilitated problematic tasks and the large effect size evinces that this was a meaningful improvement of hand function. It compares to the impact that a mobility device like a wheelchair has on daily living. Fourteen subjects found the system useful, expressing the need for such a neuroprosthesis. Examples of acquiring new abilities while using the device, indicate that the method could have a therapeutic use as well. Furthermore, results from the IPPA questionnaire are indicating what issues people with tetraplegia may hope to solve with a neuroprosthesis for the hand. The satisfaction of the device (QUEST) indicates that further effort in development should address wearability, eliminate wires, and improve the fitting procedure.